Return to community sport: leaning on evidence in turbulent times - Doherty, A.; Millar, P.; Misener, K. (Managing Sport and Leisure, 2020)
This commentary considers return to organized sport amidst the COVID-19 pandemic in the context of nonprofit community (grassroots) sport clubs that are the backbone of sport in many countries around the world. Local clubs can be vulnerable to challenging conditions at the best of times, and are at risk of significant negative impact if they cannot weather the storm of the current pandemic and resume their sport delivery. The opportunity and importance of drawing on evidence-based insights during these unprecedented times is highlighted here, by connecting examples of existing knowledge in several key areas (assessing and building capacity, embracing innovation, and adapting top-down policy directives to the local context) with the challenges facing community sport clubs. Potential directions for new research during and post-pandemic that builds on such foundational knowledge are also presented, charting a course for new inquiry that will support a more resilient community sport sector for the future.